Vaccine-associated feline sarcoma: current perspectives - Saba, Corey F (Vet Med (Auckl), 2017)
Feline injection site sarcomas (FISS; also known as vaccine-associated sarcomas) have been recognized for >20 years. Although uncommon, these tumors are iatrogenic, and vaccination against rabies and feline leukemia virus is perhaps the most common inciting cause. The exact etiopathogenesis is unknown, but it is widely accepted that inflammation induced by vaccines or other injections likely plays a critical role in tumor development. Injection site sarcomas are extremely locally invasive. Multimodal therapy, incorporating combinations of surgery, radiation therapy, and sometimes chemotherapy or immunotherapy, is recommended. However, tumor recurrences are common even with aggressive treatment, and many cats with FISS ultimately succumb to this devastating disease. While vaccination protocols play an important role in the management and control of infectious disease, veterinarians must be diligent in following established vaccination guidelines to minimize individual patient risk of FISS development. Early tumor detection and client education are also vital in the successful treatment of FISS.